Value‐Driven Design – A methodology to Link Expectations to Technical Requirements in the Extended Enterprise. Issue 1 (June 2013) - Isaksson, Ola; Kossmann, Mario; Bertoni, Marco; Eres, Hakki; Monceaux, Anne; Bertoni, Alessandro; Wiseall, Steve; Zhang, Xinwei
Abstract: Current systems engineering (SE) standards do not address 'Value' in much detail. Yet, understanding what drives the generation of stakeholder value in a given business context, is fundamental to promoting a common and clear vision throughout the extended enterprise, of what should be the focus of their early, conceptual work at all levels of development. This paper presents a Value‐Driven Design (VDD) methodology designed to strengthen the value and requirements maturation process within an extended enterprise setting. The work presented is the result of a three and a half year European program (CRESCENDO) within the aerospace sector. The VDD methodology is introduced and explained in an industrial aircraft development context and a selection of enabling methods and tools associated to the VDD methodology is presented.